On the improved distance vector routing protocol for UDP traffic - Mohamed, Mohamad Afendee; Derahman, Mohd Noor; Muhammed, Abdullah (Hikari, 2015)
The idea of Mobile Ad-Hoc Networks is to support communication where readily available infrastructure is missing. Nodes are expected to forward each other messages to the final destination within a decentralized environment. In mobile communication, finding the best routing path is always been a problem. DSDV protocol is well-known for its packet dropping problem in the event of link breakages. Whereas, IDSDV protocol as its popular enhancement, assigned to address this specific issue. But, this also gives rise to a question whether IDSDV does not degrade other performance parameters of DSDV. In this paper, we investigate the performance of IDSDV against DSDV specific for UDP traffics, for parameters such as average end-to-end delay, routing overhead and normalized routing load. Simulation result reaffirms that IDSDV has to some degree resolved the stale route problem within DSDV. Moreover, IDSDV outclasses DSDV in most aspects notably within highly density and dynamic environment.